The Sopranos. The complete first season [videorecording (DVD)] - Chase, David, 1945 August 22-; Gandolfini, James; Bracco, Lorraine, 1955-; Falco, Edie (HBO Home Video, 2000)
Tony Soprano is your average, middle-aged businessman. Tony's got a dutiful wife, a not-so-dutiful daughter, a son named Anthony Jr. a mother he's trying to coax into a retirement home, a hot-headed uncle, a not-too-secret mistress and a shrink to tell all his secrets, except the one she already knows: Tony's a mob boss.